APPLICATION OF RADIOIMMUNOASSAY DETERMINATION OF ERYTHROPOIETIN IN MONITORING OF THALASSEMIC PATIENTS - WIWANITKIT, Viroj (The ASEAN Journal of Radiology, 2023)
Erythropoietin (EPO) is a glycoprotein produced primarily by the kidney in response to hypoxia and anemia. A number of kits are available for measuring EPO, using different immunoassay techniques. Analysis of serum EPO measurement variation between methods showed evidence of significant negative bias with ELISA when compared with RIA methods. Therefore, the RIA method seems better method for determination of EPO. In this article, the author reviewed the previous studies on using EPO determination in monitoring of the thalassemic patients.